STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA GURU - Ratih Elvirawati; Mohamad Muspawi; Masbirorotni masbirorotni (STKIP Pesisir Selatan, 2023)
This study aims to summarize and describe how the principal's strategy in increasing teacher motivation. The method used in writing this scientific article is to use qualitative methods and literature review (library research). School principals have a big role to play in the formation of qualified teachers, by providing encouragement, direction, motivation, coaching and supervision that will ultimately improve their performance. School productivity is not only to get as much work as possible, but the quality for work is very important to note. The principal as a manager isi required to provide motivation to his subordinates, namely teachers as implementers of education and teaching in schools.